Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/nu11030545
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Uses, Phytochemistry and Pharmacological Properties of Elaeodendron transvaalense

Abstract: Elaeodendron transvaalense is a plant species, which is in high demand as a herbal medicine in southern Africa. This study critically reviewed the medicinal applications, phytochemistry and pharmacological activities of E. transvaalense. The literature on medicinal applications, phytochemical, and pharmacological activities of E. transvaalense, was collected from multiple internet sources including Elsevier, Google Scholar, SciFinder, Web of Science, Pubmed, BMC, Science Direct, and Scopus. Complementary infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The antimicrobial property of E. transvaalense stems bark extracts were assessed against various organisms (McGaw et al 2000;Khumalo et al 2019;Maroyi and Semenya, 2019). These findings supported the traditional usage of this species as an herbal remedy for venereal illnesses, sexually transmitted infections, stomach pains, diarrhoea, sore throat, skin infections, and wounds (Tshikalange et al 2005;Steenkamp et al 2007;Steenkamp et al 2016).…”
Section: Resultsmentioning
confidence: 60%
“…The antimicrobial property of E. transvaalense stems bark extracts were assessed against various organisms (McGaw et al 2000;Khumalo et al 2019;Maroyi and Semenya, 2019). These findings supported the traditional usage of this species as an herbal remedy for venereal illnesses, sexually transmitted infections, stomach pains, diarrhoea, sore throat, skin infections, and wounds (Tshikalange et al 2005;Steenkamp et al 2007;Steenkamp et al 2016).…”
Section: Resultsmentioning
confidence: 60%
“…Previous evaluation of DPPH and ABTS+ radical scavenging activities of E. croceum acetone leaf extract yielded significant results with IC 50 values of 7.7 and 3.1 μg/mL, respectively [ 66 ], comparing well the results obtained in this study. Maroyi [ 84 ]; Odeyemi and Afolayan [ 85 ], however, reported much lower DPPH and ABTS+ scavenging activities of E. croceum leaf and bark acetone extracts. In their study, they observed IC 50 values 0.09 and 0.1 mg/mL for the leaf extracts in ABTS and DPPH assay, while the bark extract showed activities with IC 50 of 0.2 and 0.07 mg/mL ABTS and DPPH assay, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Elaeodendron transvaalense (Burtt Davy) R. H. Archer is a medium and small deciduous tree frequently known as a bushveld saffron or anthill saffron. In Zambia, Zimbabwe, Mozambique, Swaziland, Botswana, Namibia, Angola, and South Africa, the genus is found as evergreen woods, near rivers, stony highlands, and insect piles [25]. In southern Africa, the root macerate and bark of E. transvaalense are used as herbal remedies to treat various ailments.…”
Section: Traditional Usesmentioning
confidence: 99%